Safety and efficacy of lesion size index guided 50 W radiofrequency ablation in patients with paroxysmal atrial fibrillation - Xinzhong Li; Zhiwen Xiao; Jiachen Zhang; Xiaobo Huang; Hairuo Lin; Senlin Huang; Yulin Liao; Juefei Wu; Jiancheng Xiu; Jianyong Li; Jianping Bin; Yuegang Wang (BMC Cardiovascular Disorders, 2025)
Abstract Background Pulmonary vein isolation (PVI) using conventional power (30–35 W) radiofrequency ablation (RFA) has been an effective treatment strategy for paroxysmal atrial fibrillation (PAF), but its longer duration may cause collateral damage to peripheral tissue including esophageal and phrenic nerve. High-power (HP) RFA, due to better transmural performance and shorter duration, may reduce the damage to adjacent tissue and is expected to be a safe and efficient ablation strategy. Methods In this retrospective cohort study, we included 259 patients with PAF who underwent lesion size index (LSI)-guided radiofrequency ablation. All patients underwent PVI-based ablation, and some underwent additional ablation, including superior vena cava isolation, tricuspid isthmus block, or left anterior atrial matrix modification. A total of 119 PAF patients underwent 50 W ablation. Complications and twelve-month arrhythmia-free outcomes of the procedure were compared with those of 140 patients who underwent 30–35 W ablation. Results PVI was successfully achieved in all patients. The procedural duration (140.3 ± 34.4 vs. 151.3 ± 40.6 min, P = 0.022) and overall radiation (112.0 ± 67.2 vs. 188.2 ± 119.2 mGy·cm2, P < 0.001) were significantly lower in the 50 W group. No major complications occurred in the high-power short-duration (HPSD) group, whereas in the conventional power group, five participants developed complications. Among them, three cases were related to venipuncture, one had pericardial tamponade, and one had slight pericardial effusion. The recurrence of arrhythmia at the twelve-month follow-up was not significantly different between the two groups [11 (9.2%) vs. 19 (13.6%), P = 0.278]. Conclusion LSI-guided HPSD-RFA was demonstrated to be comparably safe and efficacious compared to conventional ablation and resulted in reduced procedure time and radiation exposure. Graphical Abstract Central Illustration. Safety and Efficacy of Lesion Size Index Guided 50 W Radiofrequency ablation in Patients with Paroxysmal Atrial Fibrillation. A total of 259 patients with paroxysmal atrial fibrillation underwent lesion size index (LSI)-guided radiofrequency ablation were enrolled. High-Power Short-Duration ablation reduced total procedure time, significantly decreased radiation exposure, and had similar recurrence rate of atrial fibrillation.